Description of Albumin Levels in Type II Diabetes Mellitus Sufferers in RSUD H. A. Sulthan Daeng Radja Kab. Bulukumba - Putri, Jusnita; Ridwan, Asriyani; Asdinar, Asdinar (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: Type II diabetes mellitus is a metabolic disorder characterized by insulin resistance. Where this diabetic state affects plasma protein metabolism in the body, one of which is albumin. The occurrence of a decrease or increase in albumin levels is strongly influenced by several things including protein intake, alcohol, osmotic pressure, hormones and physiological factors. Objective: to know the picture of albumin levels in patients with type II diabetes mellitus at H. A. Sulthan Daeng Radja Hospital, Bulukumba Regency. Method: this is a descriptive research with a cross sectional approach. Results: Showed that out of 28 patients, there were 7 people with low albumin levels and 21 people with normal albumin levels. The antioxidant potential of albumin shows that it is associated with diabetes mellitus. Theoretically, uncontrolled diabetes mellitus patients have low albumin levels Based on gender, respondents were male with low albumin levels as many as 3 people (43%) and female as many as 4 people (57%). Based on age where the percentage in the age range of 30-50 years as many as 13 people (46%), for ages 51-65 years as many as 12 people (43%), and ages 66-75 years as many as 3 people (11%). Conclusion: Obtained at low albumin levels in patients with type II diabetes mellitus who are female as many as 4 people (57%) and male sex as many as 3 people (43%). Keywords: Diabetes mellitus, hypoalbuminemia, serum albumin levels